Upskilling Professional Competency of Health Workers in the Era of the Covid-19 Pandemic at Bintang Amin Hospital, Lampung - Febby Sonia; Suryanto Suryanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the need for competency improvement carried out by hospitals. Up skilling professional competency organized by the hospital aims to increase the knowledge and competence of health workers to provide optimal health services. This study used a descriptive qualitative approach and was obtained by in-depth interviews. The collected data was then analyzed using thematic analysis according to the category of the results of the interview topics. The results indicate Upskilling professional competency needs to be carried out with theoretical and practical modules so that the process of improving comprehension and putting learning into practice can be done successfully and efficiently. Upskilling professional competency includes learning related to hard skills, soft skills, patience, emotional awareness, and knowledge to deal with the Covid-19 pandemic. The results are expected that hospitals can continue to take part in Upskilling professional competency by providing regular training on topics such as patient service standards, especially for Covid-19 patients, good and effective communication, and sufficient knowledge to provide health services during the Covid-19 pandemic.